KEMAMPUAN MENULIS KARANGAN DESKRIPSI DENGAN METODE FIELD TRIP SISWA KELAS X SMA NEGERI 1 SOSOPAN - Toras Barita Bayo Angin (Institut Pendidikan Tapanuli Selatan, 2020)
The problem studied was the ability to write descriptions with the field trip method class X SMA N 1 Sosopan in terms of aspects (1) content, (2) organization, (3) vocabulary, (4) use of language, and (5) mechanics. The theoretical study used in this study refers to Agus Trianto's opinion. This type of research is quantitative by using descriptive methods. Data obtained by providing test writing essay description with a predetermined topic. The population of this study was all students of class X SMA N 1 Sosopan, totaling 135 students. The research sample of 20% of 135 students is 27 students. Based on the results of research and analysis of data on the essay description written by class X students of SMA N 1 Sosopan, it can be concluded as follows: (1) the ability to write a description of the field trip method from the aspect of content is classified as very good, ie 90 with a scale of 86-95%. (2) the ability to write a description of the field trip method from the Organizational aspect is sufficient, that is 58 on a scale of 56-65%. (3) the ability to write a description on the Aspect of using vocabulary is included in the sufficient category that is 58 on a scale of 56-65%. (4) The ability to write a description on aspects of using language is sufficient, that is 57 on a scale of 56-65%. (5) the ability to write descriptions on the mechanical aspects is very poor, 15 on a scale of 0-15%. The conclusion of the research shows that the ability to write a description essay using field trip method class X students of SMA N 1 Sosopan in Academic Year 2018/2019 is classified as good, that is 78.44 on the scale of 76-85. For further improvement it is suggested as follows: (1) Teachers should always try to encourage students to practice writing more and give more time to learning to write, because writing is a skill that is not easy, (2) students should read lots of various both fiction and non-fiction books, especially those related to writing descriptions, and students should be active and learn to explore written ideas through the field trip method.